Hemorrhagic fever with renal syndrome caused by Hantaan virus infection in four pregnant Chinese women. Issue 10 (6th June 2017) - Ji, Fanpu; Zhao, Wenxuan; Liu, Hailing; Zheng, Hongbo; Wang, Shengbang; He, Caini; Wang, Wenjun; Zhang, Ruijuan; Bai, Dan; Tian, Changyin; Zhao, Wenxue; Deng, Hong
Abstract : Hantavirus infection during pregnancy can influence both maternal and fetal outcomes. Here, we describe four cases of hemorrhagic fever with renal syndrome (HFRS) in pregnant Chinese women. The HFRS put these women at increased risk for severe illness, despite the patients' symptomologies in the onset phase were similar to those observed in non‐pregnant HFRS patients, such as fever, headache, nausea, and thrombocytopenia. Pregnant women appeared to have a more severe status, presenting with severe complications, such as hypervolemia and pulmonary edema. Nevertheless, with appropriate management, mothers with HFRS may carry to full‐term and breastfeeding maybe safe and feasible.